2019
DOI: 10.1123/ijspp.2018-0107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short Daytime Nap on Shooting and Sprint Performance in High-Level Adolescent Athletes

Abstract: The results of the research indicate varying effects of naps between sport-specific performance measures. Napping had no effect on shooting performance while a negative effect existed in 20-m sprint performance, potentially due to sleep inertia. Considering these findings, some caution is warranted when advocating naps for adolescent athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
32
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 38 publications
1
32
2
Order By: Relevance
“…These findings are in contradiction with the results of the present study and those of Waterhouse et al (2007). These discrepancies could be explained by the reduced sleep at night in the study of Suppiah et al (2018). In fact, the participants in the study of Suppiah et al (2018) were high-level Asian youth athletes who trained regularly.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings are in contradiction with the results of the present study and those of Waterhouse et al (2007). These discrepancies could be explained by the reduced sleep at night in the study of Suppiah et al (2018). In fact, the participants in the study of Suppiah et al (2018) were high-level Asian youth athletes who trained regularly.…”
Section: Discussioncontrasting
confidence: 99%
“…A few studies have been conducted analyzing the impact of napping on athletic or physical performance(Waterhouse et al, 2007; Petit et al, 2014; Blanchfield et al, 2018; Hammouda et al, 2018; Keramidas et al, 2018; Suppiah et al, 2018; Daaloul et al, 2019). Waterhouse et al (2007) showed a better sprint performance following a 30-min post-lunch nap in partially sleep-deprived athletes, with reduced mean time for both 2-m (−0.04 s) and 20 m (−0.09 s) sprints in comparison to a no-nap condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies are limited by the lack of an objective measurement of the previous night’s sleep [ 11 , 12 , 13 , 15 , 16 , 17 , 28 ], which may confound their results. In this study, we confirmed total time sleep before each condition via the use of actigraphy, similar to previous work [ 14 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 90%